Computed Tomography and Magnetic Resonance Imaging Features of the Temporomandibular Joint in Two Normal Camels. (20th October 2011) - Arencibia, Alberto; Blanco, Diego; González, Nelson; Rivero, Miguel A.
Abstract : Computed tomography (CT) and magnetic resonance (MR) image features of the temporomandibular joint (TMJ) and associated structures in two mature dromedary camels were obtained with a third-generation equipment CT and a superconducting magnet RM at 1.5 Tesla. Images were acquired in sagittal and transverse planes. Medical imaging processing with imaging software was applied to obtain postprocessing CT and MR images. Relevant anatomic structures were identified and labelled. The resulting images provided excellent anatomic detail of the TMJ and associated structures. Annotated CT and MR images from this study are intended as an anatomical reference useful in the interpretation for clinical CT and MR imaging studies of the TMJ of the dromedary camels.